Auditoría de gestión y su incidencia en el desempeño académico de la unidad educativa 16 de Mayo, cantón Quinsaloma, año 2013 - Luna Mindiola, Elena Lucrecia (2015)
The research project contains general objective determine the incidence of Auditing in the academic performance of the Education Unit May 16th, located in Canton Quinsaloma street May 16 and San Francisco, to analyze each of the activities institution; for the purpose of determining the degree of efficiency and effectiveness in the performance that took place in 2013. The Audit Management review activities allowed during that period, in order to assess the administrative development of the institution, because through Documentary, exploratory and bibliographic could issue recommendations to make the best decisions on behalf of the institution. One of the main objectives that had the audit within the Education Unit was to determine the degree of compliance with the goals and objectives could evaluate the performance that took each of the members who are involved in activities. This research project allowed us to detect the different weaknesses; they have not been allowed to develop efficiently. As a result of the investigation it was determined that the Education Unit "May 16" has not fully complied with the planned activities to ensure student quality, student satisfaction with academic and ensure compliance with quality standards due a lack of audit. For which appropriate recommendations are made by the issuance of the final report which disclosed the shortcomings found. Administrative able to take precise to give the opportunity to improve efficiently for the benefit of the institution decisions.